2017
DOI: 10.4172/2168-9296.1000188
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Autophagy in Retinal Pigment Epithelial Cells Induced from iPS Cells obtained from a Patient with Sialidosis

Abstract: Sialidosis type I patient-derived induced pluripotent stem cells (iPSCs) were generated from blood mononuclear cells. During embryoid body-like 3D culture, aggregates of patient-derived iPSCs were irregular in shape and had increased vacuoles filled with lipid droplets and cellular components such as damaged mitochondria. Retinal pigment epithelial cells induced from patient-derived iPSCs showed impaired autophagy flux with decreased formation of LC3 puncta. Sialidosis patient-derived iPSCs could provide a use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The sialidosis-iNPCs (G227R-iNPCs and V275A/R347Q-iNPCs) exhibited brightly stained large, perinuclear-clustered, and scattered lysosomes in the peripheral region, while the normal-iNPCs showed lightly stained, smaller lysosomal vesicles with less perinuclear clustering ( Figure 4 A, red). Increasingly, studies have demonstrated that impaired lysosomal function observed in various LSDs is associated with autophagy impairment [ 22 , 28 , 29 , 30 ]. Unstimulated basal levels of autophagic vacuoles were not detectable in either normal- or sialidosis-iNPCs by the CYTO-ID autophagy detection assay; thus, we evaluated the impact of rapamycin, an mTOR-dependent autophagy inducer [ 31 ], in the sialidosis-iNPCs and compared them to normal-iNPCs ( Figure 4 A,B, green).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sialidosis-iNPCs (G227R-iNPCs and V275A/R347Q-iNPCs) exhibited brightly stained large, perinuclear-clustered, and scattered lysosomes in the peripheral region, while the normal-iNPCs showed lightly stained, smaller lysosomal vesicles with less perinuclear clustering ( Figure 4 A, red). Increasingly, studies have demonstrated that impaired lysosomal function observed in various LSDs is associated with autophagy impairment [ 22 , 28 , 29 , 30 ]. Unstimulated basal levels of autophagic vacuoles were not detectable in either normal- or sialidosis-iNPCs by the CYTO-ID autophagy detection assay; thus, we evaluated the impact of rapamycin, an mTOR-dependent autophagy inducer [ 31 ], in the sialidosis-iNPCs and compared them to normal-iNPCs ( Figure 4 A,B, green).…”
Section: Resultsmentioning
confidence: 99%
“…Sialidosis-iPSCs, harboring both sialidosis-associated mutations and patient-specific genetic background, offer emerging opportunities to investigate sialidosis at the cellular and molecular level. However, only four reports have been published on sialidosis-iPSC models from patients with different NEU1 mutations [ 21 , 22 , 23 , 24 ]. Two reports demonstrated the establishment of sialidosis-iPSC models with NEU1 mutations c.649G > A/644 T > C, c.1109A > G/c.1109A > G [ 43 ], c.1195_1200dup/c.679G > A [ 23 , 32 ], or c.544 A > G transition and 667–679 deletion from sialidosis patient fibroblasts [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis aligns with previous evidence of dysregulated autophagy-lysosomal system in the retinal pigment epithelium of Type 1 sialidosis, suggesting that the damaged retinal pigment epithelium disrupts the blood-retinal barrier, thereby increasing the permeability of choroidal capillaries. 4 The abnormal photoreceptor cell homeostasis caused by retinal pigment epithelium dysfunction may affect the foveola, the highest cone photoreceptor area with high energy demand, to a greater extent and contribute to transretinal hyperreflectivity. 5 Further research is required to explore this connection.…”
mentioning
confidence: 99%